The Neglected Potential of Rothbard’s Preface to Theory and History as an Introductory Text on Austrian Methodology - Pickering, George (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2021)
Given the breadth of the ideas of the Austrian School of Economics and the numerous lengthy treatises across which those ideas are scattered, it is difficult to recommend an introductory text that conveys its definingcharacteristics. However, in this regard, Murray N. Rothbard’s rarely discussed Preface to Ludwig von Mises’s book Theory and History possesses considerable untapped potential. The Preface’s merits as an introductory reading stem not only from its persuasive summary of the praxeological method and the core arguments in its favor, amongst other distinguishing characteristics of the Austrian School, but also from its brevity and Rothbard’s stilistic clarity, which make it incredibly accessible to newcomers to Austrian ideas.